Going home again? Fan nostalgia in anticipation of World of Warcraft Classic - Toft-Nielsen, Claus (MedieKultur: Journal of media and communication research, 2019)
Since its release in 2004, World of Warcraft (WoW) has regularly changed the game and the play experience in significant ways. Recently, Blizzard, the developer of WoW, announced the upcoming game WoW Classic: “an authentic, Blizzard-quality classic experience”. Drawing on interviews with adult WoW fans and gamers, the article examines the game as an ‘affective space’ (Hills, 2002) of fandom that cannot be separated from the fan narratives and experiences it mediates. A key component in this affective space is the notion of fan nostalgia. The nostalgic relationship between a fan and a favourite text is often imbued with an imagined history, conjoining aff ect and meaning, belief and knowledge, and making nostalgia “both a way of knowing worlds – and a discourse of knowledge” (Radstone, 2010, p. 188). The article traces diff erent and often contradictory modes of fan nostalgia connected to WoW, such as tactile feelings of technostalgia (Bolin, 2015), deeply personal and anchoring types of nostalgia in the form of totemic objects (Proctor, 2017), manifested through fan practices of collecting digital items and souvenirs (Geraghty, 2014), and interwoven with desirable and appropriate self-identity and self-narrative (Williams, 2014). In reading these modes of nostalgia, the article argues that they ultimately function as a sort of ‘homecoming’, as the gamers’ many different experiences of the game and media texts surrounding the game all come together as complex attempts of memory work, creating the possibility of establishing a home within their fandom.